Colistin potentiation in multidrug-resistant Acinetobacter baumannii by a non-cytotoxic guanidine derivative of silver - Kumar, Deepak; Singhal, Chaitali; Yadav, Manisha; Joshi, Pooja; Patra, Priyanka; Tanwar, Subhash; Das, Amitava; Kumar Pramanik, Sumit; Chaudhuri, Susmita (Frontiers in Microbiology, 2023)
A novel nano-formulation (NF) that sensitizes Acinetobacter baumannii (AB) to otherwise ineffective colistin, is described in the present study. Infections due to multi-drug resistant (MDR) AB represent a major therapeutic challenge, especially in situations of pre-existing colistin resistance. Subsequently, boosting the effectiveness of colistin would be a better alternative tactic to treat AB infections rather than discovering a new class of antibiotics. We have previously demonstrated a NF comprising self-assembled guanidinium and ionic silver nanoparticles (AD-L@Ag(0)) to have anti-biofilm and bactericidal activity. This is the very first time this NF AD-L@Ag(0) is being reported for potentiation of colistin in Gram negative colistin-resistant bacteria. Our results implied that a combination of clinically relevant concentrations of colistin and AD-L@Ag(0) significantly decreased colistin-resistant AB bacterial growth and viability which otherwise was elevated in the presence of only colistin. Here we have described various combinations of minimum inhibitory concentration (MIC) of colistin (MICcol, ½ MICcol, and ¼ MICcol) and that of AD-L@Ag(0) (MICAD-L@Ag(0), ½ MICAD-L@Ag(0), and ¼ MICAD-L@Ag(0)), tested against MDR AB culture. The results (in broth as well as in solid media) signified that, AD-L@Ag(0) was able to potentiate the anti-microbial activity of colistin at sub-MIC concentrations. Further, the viability and metabolic activity of bacterial cells were also measured by CTC fluorescence assay and ATP bioluminescence assay. The results of these assays were in perfect concordance with the scores of cultures (CFU and culture turbidity). Additionally, qRT-PCR was performed to unveil the expression of selected genes DNAgyrA, DNAgyrB and dac. These genes introduce negative supercoiling in the DNA, and hence are important for basic cellular processes. These genes due to mutation, modified the Lipid A of bacteria, further resisting the uptake of colistin. That is why the expression of these genes was upregulated when AB was treated with only colistin; substantiating that AB is resistant to colistin. Whereas the combinations of MICcol + MICAD-L@Ag(0) downregulated the expression of these genes, implying that the developed formulation can potentiate the efficiency of colistin. Conclusively, AD-L@Ag(0) can potentiate the proficiency of colistin; further enhancing colistin-mediated death of AB, by putatively disrupting outer-membrane and facilitating bacterial death.